Internal traction as a surgical option in type III long-gap esophageal atresia: A case series - Darling Zamorano; Marcela Santos; Alicia Gómez; Isidora Lavado; Miguel Guelfand (Elsevier, 2023)
Introduction: Long-gap esophageal atresia (LGEA) is an important challenge for pediatric surgeons. Multiple techniques have been described to restore the esophageal continuity in patients with this complex condition. The aim of this study is to describe our experience and results in the repair of type III LGEA using thoracoscopic internal traction without gastrostomy. Case presentation: A retrospective review of three patients with type III LGEA who underwent thoracoscopic internal traction in the Pediatric Surgery Service of the Exequiel González Cortés Children's Hospital between 2018 and 2022 was performed.The patients were newborns between 36 and 39 weeks of gestational age, with a birth weight between 1800 and 3000 g. All of them diagnosed with type III LGEA. They underwent the same procedure, which consisted of internal traction of the bags with Prolene ® sutures and clips in each esophageal bag for its fixation. The mean age was 2.3 days at the first intervention and 16 days at the esophageal anastomosis. An esophagram was performed one week after the anastomosis and showed no signs of leakage or stricture. Median follow-up was 27 months (range, 10 months - 4 years). Two of the patients developed esophageal stricture 6 months after the anastomosis and required endoscopic dilation. Two patients developed gastroesophageal reflux, which was managed medically. Conclusions: In our experience, the thoracoscopic internal traction technique with delayed anastomosis is a safe option for patients with LGEA type III. In addition, postoperative complications commonly seen with tight end-to-end anastomoses are avoided.